KONSEKWENSI PRESIDEN TANPA DUKUNGAN MAYORITAS DI PARLEMEN - Supriyadi Supriyadi (University of Merdeka Malang, 2017)
Every time a President and/or vice President was/ were new, the first thought was how the government administration that would be formed could get support from parliament. It was natural. Both presidential and parliamentary government system had to involve legislative assembly as the realization of democratic government and also the implementation of indirect democracy system. In the context of authority relation between President and legislative assembly based on Constitution 1945, it sometimes became a problem when President and/or vice President was/were not supported by the majority members of legislative assembly.It could make confusion of President and/or vice President in carrying out state government administration because there was no support toward the working program which had been planned. And even because of much worries, impeachmentcould be done. However, constitution 1945 gave a strong position to President and/or vice President as the consequence of the implementation of Presidential, so the worry did need to occur. Setiap terpilihnya Presiden dan/atau Wakil Presiden baru, pikiran yang mencuat pertama kali biasanya adalah bagaimana pemerintahan yang akan dibentuk tersebut memperoleh dukungan dari parlemen (DPR). Hal ini wajar, baik sistem pemerintahan presidensiil apalagi parlementer harus melibatkan lembaga perwakilan rakyat sebagai wujud pemerintahan yang demokratis dan sekaligus implementasi indirect democracy system. Dalam konteks hubungan kewenangan antara Presiden dengan DPR berdasarkan UUD 1945, kadang menjadi ganjalan ketika Presiden dan/atau Wakil Presiden tidak didukung mayoritas anggota DPR. Hal tersebut bisa saja menimbulkan kegalauan Presiden dan/atau Wakil Presiden dalam menjalankan pemerintahan negara, karena tidak adanya dukungan terhadap program kerja yang telah dicanangkan, bahkan kekhawatiran yang berlebih bisa saja dilakukan impeachment. Namun demikian, dengan berlakunya UUD 1945 saat ini yang memberikan kedudukan kuat kepada Presiden dan/atau Wakil Presiden sebagai konsekwensi diterapkannya sistem pemerintahan presidensiil, maka kekhawatiran itu tidak perlu terjadi.